Spectrophotometric Determination of Atenolol via Oxidative Coupling Reaction with 2, 4 - Dinitrophenyl Hydrazine - Raed M. Hussein (Journal of Global Pharma Technology, 2019)
An correct and sensitive spectrophotometric methodology has been developed for the determination of beta-adrenergic blocker (ATN) in pure and dose forms. the strategy is predicated on the oxidization of 2,4-dinitrophenylhydrazine (2,4-DNPHz) by metallic element per iodate than coupling with beta-adrenergic blocker (ATN) in a calescent medium to create actable, Yellow colored , soluble dye with a most absorption at 403 nm. The variables that have an effect on the completion of reaction are fastidiously optimized. Beer’s law is obeyed over the concentration vary of (2-30 μg.mL-1) with molar absorption factor of (3.515×104 L.mol-1.cm1).The limit of detection was (0.07575μg.mL-1) and Sandal's sensitivity price was 0.0350 μg.cm-1. The projected methodology has been applied with success to the determination of antihistamine in pharmaceutical preparation.